Synthesis of imidazopyridine-fused indoles via one-pot sequential Knoevenagel condensation and cross dehydrogenative coupling. Issue 33 (10th August 2018) - Shinde, Vikki N.; Dhiman, Shiv; Krishnan, Rangan; Kumar, Dalip; Kumar, Anil
Abstract : Synthesis of imidazopyridine-fused indoles has been developed via one-pot sequential Knoevenagel condensation followed by palladium-catalyzed intramolecular cross-dehydrogenative coupling reaction. Abstract : A simple and efficient strategy for the synthesis of imidazopyridine-fused indoles has been developed that involves one-pot sequential Knoevenagel condensation of readily available active methylene azoles with N -substituted-1 H -indole-3-carboxaldehydes or N -substituted-1 H -indole-2-carboxaldehydes followed by palladium-catalyzed intramolecular cross dehydrogenative coupling reaction. A series of 36 derivatives was prepared by using this strategy. The products were obtained in moderate to excellent (32–94%) yields and showed broad substrate scope with tolerance of various functional groups and was amiable for gram scale preparation without problems.